5
$\begingroup$

Recently I was asked about the uniqueness of the solutions of the equation $y'=y$. It could be obtained by multiply $e^{-x}$.

This time I was wondering about the same question regarding a different equation. We know that the solutions of $y''+y=0$ are of the form $a\sin(x)+b\cos(x) $.

How can we explain that these are the ONLY solutions?

$\endgroup$
3
$\begingroup$

We shall show that every solution of the equation $y''+y=0$ is of the form $y(x)=a\cos x+b\sin x$, for some $a,b\in\mathbb R$.

In particular, we shall show that $$y(x)=y(0)\cos x+y'(0)\sin x$$ or equivalently $\,z(x)\equiv 0,\,$ where $z(x)=y(x)-\big(y(0)\cos x+y'(0)\sin x\big)$.

First of all, it can be readily shown that $$ z''(x)+z(x)=0, $$ and $$ z(0)=z'(0)=0. \tag{1} $$ Hence $$ 0=z'(z''+z)=z'z''+zz'=\frac{1}{2}\big((z')^2+z^2\big)' $$ and thus $w(x)=\big(z(x)\big)^2+\big(z'(x)\big)^2$ is a constant function, and in particular $w(x)=w(0)$ $$ \big(z(x)\big)^2+\big(z'(x)\big)^2=w(x)=w(0)=\big(z(0)\big)^2+\big(z'(0)\big)^2=0. $$ Thus $z\equiv 0$.

$\endgroup$
2
$\begingroup$

Consider the change of variable $$y' = x$$ Then you get the following ODE system: $$\begin{cases}x' =-y\\y'=x\end{cases}$$ which is of the form $$\begin{pmatrix}x'\\y' \end{pmatrix} = \begin{pmatrix}0&-1\\1&0 \end{pmatrix}\begin{pmatrix}x\\y \end{pmatrix} = A\begin{pmatrix}x'\\y' \end{pmatrix}$$ where $A$ is the fundamental matrix. Therefore, you have a linear homogeneous differential equation with constant coefficients which is explicitly solvable. You can find a proof here with some examples.

$\endgroup$
0
$\begingroup$

Using $z(t)=y(t)\cos (t+a)-y'(t)\sin (t+a)$ you get $$ z'(t)=-(y(t)+y''(t))\sin(t+a)=0 $$ so that $z$ is constant without deviation, with the constant uniquely determined by the initial condition, so that for all $a$ $$ y_0\cos(a)-y'_0\sin(a)=y(t)\cos (t+a)-y'(t)\sin (t+a). $$ Now substitute $a=-t$ (or $t=-a$) to get, also uniquely, $$y(t)=y_0\cos(t)+y'_0\sin(t).$$

$\endgroup$
0
$\begingroup$

You can also solve it easily

$$y''=-y$$ for $y \neq 0$ $$ \frac {y''}{y}=-1$$ $$ \left (\frac {y'}{y} \right)'+\left( \frac {y'}{y}\right )^2=-1$$ Substitute $z=\frac {y'}y$ $$z'+z^2=-1$$ That's separable $$\int \frac {dz}{z^2+1}=-x+K \implies \arctan(z)=K-x $$ $$y'=y\tan (K-x)$$ $$y'\cos(K-x)-y\sin(K-x)=0$$ $$y=C_1\cos(x+C_2)$$

$\endgroup$
  • $\begingroup$ unm.. i have two questions for your answer. First can we multiply by y'? I think we shold be careful for this because we don't have ANY equation for for y'. Second how can I solve the last line of your equation? $\endgroup$ – 김기훈 May 18 '18 at 0:29
  • $\begingroup$ I added a complete solution I hope it's more clear..@김기훈 $\endgroup$ – Isham May 18 '18 at 18:42

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.